Authenticity and well-being: Exploring positivity and negativity in interactions as a mediator. (15th July 2017) - Baker, Zachary G.; Tou, Reese Y.W.; Bryan, Jennifer L.; Knee, C. Raymond
Abstract: Personality-level authenticity is a robust predictor of both well- and ill-being. Recent research has explored the ways in which this element of personality is associated with interpersonal relationships and interactions. The present study examines the valence of interpersonal interactions (i.e., positivity and lack of negativity) as a mediator of the associations between authenticity and well-/ill-being. Participants reported authenticity at baseline, recorded their perceptions of valence for each interaction in which they participated for two weeks, and reported several indicators of well- and ill-being at follow-up. We then averaged each interaction valence report within participants to get a participant-level (i.e., chronic) measurement of interaction valence. Results revealed that authenticity positively predicted well-being and that interaction valence mediated these associations. These same mediation analyses were not significant for ill-being, though all results were in the predicted directions. Results were interpreted as evidence suggesting that the personality trait of authenticity has implications for interaction with others and that these interactions, in turn, may have implications for one's state of being. Highlights: Authenticity benefits interpersonal relationships and individual well-being. We proposed that interactions might explain why authenticity benefits well-being. Interpersonal interactions mediated the authenticity - well-being association. A similar model was not supported for the authenticity – ill-being association.